2022
DOI: 10.3390/ani12101251
|View full text |Cite
|
Sign up to set email alerts
|

The Early Prediction of Common Disorders in Dairy Cows Monitored by Automatic Systems with Machine Learning Algorithms

Abstract: We use multidimensional data from automated monitoring systems and milking systems to predict disorders of dairy cows by employing eight machine learning algorithms. The data included the season, days in milking, parity, age at the time of disorders, milk yield (kg/day), activity (unitless), six variables related to rumination time, and two variables related to the electrical conductivity of milk. We analyze 131 sick cows and 149 healthy cows with identical lactation days and parity; all data are collected on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Accelerometers can also monitor rumination [ 66 ]. It has been widely demonstrated that monitoring rumination can be very useful for accurately predicting and diagnosing multiple disorders in dairy cows [ 67 ]. Although it is not widely used in fattening units, it has been demonstrated that animals suffering from BRD had a lower rumination index compared to healthy ones at three to six days before the onset of clinical signs [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accelerometers can also monitor rumination [ 66 ]. It has been widely demonstrated that monitoring rumination can be very useful for accurately predicting and diagnosing multiple disorders in dairy cows [ 67 ]. Although it is not widely used in fattening units, it has been demonstrated that animals suffering from BRD had a lower rumination index compared to healthy ones at three to six days before the onset of clinical signs [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…In cows, individual cows were not more similar than different cows across days, when a clustering was applied on activity and area use in the barn per minute (Stachowicz et al , 2022). However, classification of different features of 24-h patterns may help discriminate between healthy and sick cows prior to clinical symptoms (Stachowicz et al , 2022; Zhou et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of disease on rumination time in cows has been described in many studies, most recently by Zhou et al (2022), who showed that rumination duration in diseased cows decreased compared with healthy cows prior to clinical signs. Moreover, the diseased cows displayed an increase in the ratio of rumination time at daytime compared to nighttime, indicating a deviance in timing from their normal rhythm (Zhou et al, 2022). Both nighttime rumination time and the ratio between daytime and nighttime rumination time, as well as the difference between recorded and expected rumination time per 2-h, were important features for the prediction of healthy vs. diseased cows using classification models.…”
Section: Individual Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the health monitoring of ruminants such as cows and sheep has become increasingly important. (1)(2)(3)(4)(5)(6) In particular, pH monitoring of the cow's rumen has attracted attention because of the strong relationship between the pH and the deadly disease of rumen acidosis. (7)(8)(9) Giving cows rapidly digestible carbohydrates, which is effective for the stable production of rich milk and marbled beef, can cause rumen acidosis.…”
Section: Introductionmentioning
confidence: 99%